A new criterion for controlling edge localized modes based on a multi-mode plasma response. (18th October 2019) - Gu, S.; Wan, B.; Sun, Y.; Chu, N.; Liu, Y.Q.; Shi, T.; Wang, H.H.; Jia, M.; He, K.
Abstract: A new technique for multi-mode plasma response extraction is presented, as well as a new criterion to identify modes associated with edge localized mode (ELM) control. This technique extracts modes by separating the full poloidal cross-section structure from the phase difference between upper and lower resonant magnetic perturbation (RMP) coils . The dependence of extracted modes are compared to the effect of ELM control using both n = 2 and n = 3 RMP in wide q 95 operating regimes. It shows that the mode with highest resonant plasma response near the pedestal top is correlated with ELM mitigation or suppression, even if the mode is not the dominant one in plasma response.